Clinical nursing competency assessment: a scoping review - Anim-Boamah Oboshie; Christmals Christmal Dela; Armstrong Susan Jennifer (Sciendo, 2021)
To ensure that only competent graduates are licensed to practice nursing, councils conduct licensing examinations, which may include among others clinical competency assessment. This review explored current practices in clinical competency assessment of nursing students as part of a larger study aimed at developing an evidence-based, context-specific framework for clinical competency assessment in a sub-Saharan African (SSA) country.